Integration of Sustainable Development Goals (SDGs) in Sustainability Reporting of Indonesia’s Healthcare Sector: A Triple Bottom Line Perspective - Alzulin Olvica Saputri; Firman Tatariyanto; Sugiyanto Sugiyanto (MASI Mandiri Edukasi, 2026)
Integration of Sustainable Development Goals (SDGs) in sustainability reporting within Indonesia’s healthcare sector remains fragmented and predominantly symbolic, creating a misalignment between global expectations and actual disclosure practices. This study aims to analyze how healthcare organizations integrate SDG-related information within the Triple Bottom Line (TBL) framework, and to compare disclosure patterns between state-owned and private institutions in order to evaluate whether sustainability reporting functions as a tool for substantive transformation or merely as a legitimacy mechanism. Using a qualitative content analysis approach, 45 sustainability and annual reports from 15 healthcare organizations (2 state-owned and 13 private) covering the period 2021–2023 were examined with NVivo 15 through open coding, thematic analysis, and matrix queries based on People, Planet, and Profit dimensions and six priority SDGs (SDG 3, 5, 8, 9, 12, 13). The results show that SDG integration is highly unbalanced: SDG 3 accounts for 45% of coded references, followed by SDG 8 (22%) and SDG 12 (15%), while SDG 13 represents only 2% of disclosures, indicating systematic underemphasis of climate action and environmental accountability. People and Profit dimensions clearly dominate reporting, with the Planet dimension receiving minimal attention, and state-owned hospitals focusing more on social legitimacy narratives. In contrast, private institutions emphasize profit-oriented and efficiency-driven disclosures, both with weak cross-dimensional integration and limited quantifiable performance indicators. The study concludes that sustainability reporting in Indonesia’s healthcare sector primarily serves legitimacy and stakeholder management purposes rather than driving authentic organizational change, and proposes the Health SDGs Integration Matrix as a practical framework for assessing SDG alignment quality and supporting the development of sector-specific regulatory guidance.